A field guide to color a watercolor workbook - Solomon, Lisa (Boulder, CO Roost Books, 2019)
"Color is one of the most profound ways we have to express ourselves. In this lively workbook for artists, graphic designers, hobbyists, and creators of all types, you will journal your way through fresh and enriching ways to develop a more personal connection to color in your art and life. Using watercolors, gouache, or any other water-based medium, dive into color theory and explore your personal style while playing with a balanced blend of experiments and color meditations. Discover a personal color wheel while exploring tints and shades. Experiment with color mixing while you make as many of one color as you can – and then name them all (honeydew green, avocado green, mint ice cream…). Through playful prompts and inspiring examples, and with lots of room for painting, this book will guide you to a new or expanded relationship with color and deepen your understanding of what color can do for you."--
Exercises--
Make a traditional color wheel with tints and shades--
Make a personal color wheel with tints and shades--
Different color schemes--
Charting your paint box--
Saturation--
Make as many of one color as you can (and name them)--
Four ways to black--
Wait, there is more than one kind of white too?--
Mixing complements--
Favorite color versus least favorite color--
Starburst color matching--
Organize something by color--
Paint chip matching exercise--
Observe and document colors in your world--
Level up inspired by Joseph Albers--
Includes bibliographical references
Keywords: Color in art; Painting -- Technique